A study of electron momentum density in Ti_Al system. - Abdul kader A. Hassan; Fareed M. Mohammed; Sameh H. Salih; Shalash A. Mohammed (Tikrit Journal of Pure Science, 2018)
We present the electron momentum densities of TiAl , Ti3Al and TiAl3 alloys in terms of Compton profile. Compton profiles (CP) of Ti and Al metals were calculated by adopting the renormalized free atom (RFA) and free electron models and choosing (3d3 – 4s1) configuration to Ti and (3s2 – 3p1) to Al as best electron configurations. The Compton profiles values were obtained by the Superposition model for the three intermetallic alloys. The theoretical results were compared with the experimental values. The present work results of TiAl , Ti3Al and TiAl3 alloys are in good agreement with the experimental values.